A two-dimensional hydro-morphological model for river hydraulics and morphology with vegetation. (February 2017) - Guan, Mingfu; Liang, Qiuhua
Abstract: This work develops a two-dimensional hydro-morphological model which can be used to simulate river hydraulics and morphology with various vegetation covers. The model system consists of five modules, including a hydrodynamic model, a sediment transport model, a vegetation model, a bank failure model and a bed deformation model. The secondary flow effects are incorporated through additional dispersion terms. The core components of the model system solve the full shallow water equations; this is coupled with a non-equilibrium sediment transport model. The new integrated model system is validated against a number of laboratory-scale test cases and then applied to a natural river. The satisfactory simulation results confirm the model's capability in reproducing both stream hydraulics and channel morphological changes with vegetation. Several hypothetical simulations indicate that the model can be used not only to predict flooding and morphological evolution with vegetation, but also to assess river restoration involving vegetation. Highlights: We developed a novel coupled flow-sediment-vegetation model. The model was tested against both laboratory-scale cases and a natural river. The model is capable of reproducing river hydraulics and morphology with vegetation. Vegetation affects localised stream hydraulics, river planform and ecological diversity.